2017
DOI: 10.15439/2017f89
|View full text |Cite
|
Sign up to set email alerts
|

The ICT adoption in enterprises in the context of the sustainable information society

Abstract: Abstract-This study, part of an ongoing global study, aims to advance information society research and practice by examining and understanding the information and communication technologies (ICT) adoption in enterprises in the context of the sustainable information society (SIS). In this study, the ICT adoption is described by four components. i.e. outlay on ICT, information culture, ICT management, and ICT quality, whereas the sustainability is composed of ecological, economic, socio-cultural, and political s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…This results mainly from difficulties in determining diagnostic criteria . During recent years, we can observe an intense development of electronic services, including entertainment (Ziemba, 2016;Ziemba 2017).…”
Section: Distribution Of Variablesmentioning
confidence: 99%
“…This results mainly from difficulties in determining diagnostic criteria . During recent years, we can observe an intense development of electronic services, including entertainment (Ziemba, 2016;Ziemba 2017).…”
Section: Distribution Of Variablesmentioning
confidence: 99%
“…With regard to the presented results, it is reasonable to conclude that this study expands the existing research on the SIS provided by Schauer [7], Fuchs [1], [2], Hilty et al [4], [5], Guillemette, Paré [14, [15], and Curry and Donnellan [12], [13] by presenting the levels of ICT adoption and sustainability as well as identifying how the ICT adoption influence sustainability. The research outputs are also complementary with findings related to the effect of ICT adoption on sustainability in enterprises [21], [22], [23] and households [48]. Summarizing up-to-date research findings, it can therefore be concluded that the ICT quality, ICT management, and information culture within enterprises and households have a significant impact on sustainability, whereas in government units only the ICT quality and information culture influence sustainability.…”
Section: A Research Contributionmentioning
confidence: 78%
“…A composite index for the SIS with subindexes of ICT adoption and sustainability in government units should be explored. In addition comparisons between government units and enterprises [21], [22], [23] may be made.…”
Section: Research Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be actualized in organizations. Based on perception of models of innovation adoption of IS security, organizational and individual levels should be analyzed [34].…”
Section: Theoretical Backgroundmentioning
confidence: 99%